2022
DOI: 10.3390/ijms23168833
|View full text |Cite
|
Sign up to set email alerts
|

An Effective Approach to Improve the Thermal Conductivity, Strength, and Stress Relaxation of Carbon Nanotubes/Epoxy Composites Based on Vitrimer Chemistry

Abstract: An effective method was developed to improve the interfacial interaction between Mutiwalled carbon nanotubes (MWCNTs) and epoxy matrix. The performance of thermal conductivity and strength of the epoxy vitrimer were enhanced by polydopamine (PDA) coating. Polydopamine is a commonly used photothermal agent, which of course, was effective in modifying MWCNTs used in photoresponsive epoxy resin. The surface temperature of the epoxy composite with 3% MWCNTs@PDA fillers added increased from room temperature to 215 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 32 publications
(37 reference statements)
0
15
0
Order By: Relevance
“…Moreover, the crack-healing time was compared with those of other classes of vitrimer materials reported in the literature (Figure ). It could be found that the repair rate of ETOD-SA-Fe 3 O 4 was much faster than those of the reported ones in the literature, and the healing efficiency under near-infrared irradiation was higher than that of heating. …”
Section: Resultsmentioning
confidence: 67%
“…Moreover, the crack-healing time was compared with those of other classes of vitrimer materials reported in the literature (Figure ). It could be found that the repair rate of ETOD-SA-Fe 3 O 4 was much faster than those of the reported ones in the literature, and the healing efficiency under near-infrared irradiation was higher than that of heating. …”
Section: Resultsmentioning
confidence: 67%
“…Light initiated SMPs are capable of mitigating issues caused by electromagnetic interference when using remote controlling, as is the reverse, in electrically or magnetically induced SMPs. [ 75 ] Two major mechanisms occurring in light induced SMPs include photochemical reactions resulting in deformation [ 76 ] as well as particulates usage capable of light conversion to heat. Regarding to photochemically affiliated reactions, works have inculcated light‐responsive substrates such as cinnamic entities [ 77 ] or molecules, [ 78 ] capable of altering the architecture of the cross‐linked polymeric network.…”
Section: Light‐responsivity Of Smp Nanoarchitecturesmentioning
confidence: 99%
“…To realize the non-contact, [16][17][18] remotely controllable, [19] and locally precise shape manipulation, [20] the light-responsive solid-state plasticity of the thermoset polymers should be investigated. Currently, the light-responsive properties of the materials can be mainly obtained by incorporating photothermal fillers such as MXene, [21][22][23][24][25] graphene, [26][27][28][29] carbon nanotubes, [30][31][32][33][34] gold nanoparticles [35,36] into the polymers. However, the addition of photothermal fillers into the polymers will inevitably lead to some side effects, which may change the overall structure of the material and thus destroy the mechanical performance.…”
Section: Introductionmentioning
confidence: 99%